Cultivating Social Attitudes Through Social Studies Learning In Elementary Schools - Herman, Herman; Widya, Prita; Nurhalisah, Nika; Setiawati, Diah; Lita, Nurfika (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Social studies learning is very necessary to shape the social attitudes of the younger generation. The younger generation acts as the pillar and spearhead of the nation's future, so that students must have good social attitudes in society and as a state. Social studies learning has a very important role in creating social attitudes in each student. The role of social studies learning, apart from developing aspects of students' knowledge, understanding and analytical skills regarding the social conditions of society, social studies learning is also predicted to play an active role in forming students' social attitudes. This research method uses literature review studies such as journals, articles, books and other sources related to social studies learning, instilling social attitudes in students, as well as the role of teachers in instilling social attitudes in each student. The results of this research reveal that the process of forming social attitudes, especially in the context of social studies learning, is an important aspect that must be carried out by teachers in the classroom in educating students. Activities to instill social attitudes through social studies learning can be instilled through social studies learning. Social studies learning can be implemented by incorporating social attitude values into students through strategies or learning systems that involve imitation elements or concrete model rolls through the habituation of other social attitudes such as honesty, discipline, responsibility, tolerance, mutual cooperation, politeness or politeness. , and confident. Social attitudes will be embedded and reflected in daily activities as seen from the learning process implemented by the teacher in social studies learning in the classroom.